(untitled) (Research, Society and Development, 2026)
This study aims to analyze hormonal differences between men and women and understand how these variations influence the practice of physical exercise, highlighting the importance of personalizing training programs according to hormonal profiles, especially considering the female menstrual cycle. This is a narrative literature review conducted using scientific articles indexed in relevant databases. The analyzed topics included hormonal physiology; the effects of testosterone on muscle strength and hypertrophy; the influence of estrogen on recovery and aerobic endurance; the role of progesterone in thermoregulation and fluid retention; and performance variations related to menstrual cycle phases and hormonal contraceptive use. The findings showed that hormonal differences significantly influence physical performance. Testosterone was associated with greater muscle strength, hypertrophy, and oxygen transport capacity in men. Estrogen contributed to improved muscle recovery, lipid metabolism, and anti-inflammatory responses in women. Progesterone was related to increased fatigue and thermoregulation changes. Performance variations were also observed according to menstrual cycle phases and hormonal contraceptive use. Hormonal differences between men and women directly affect responses to physical exercise, reinforcing the need for individualized training strategies. Considering hormonal profiles—especially menstrual cycle variations—is essential to optimize performance, prevent injuries, and promote safer and more inclusive exercise practices.